Effect of fibre type and utilisation rate on dimensional stability and frost resistance of pavement mortar mixture. Issue 1 (6th December 2023) - Kaya, Yahya; Biricik, Öznur; Bayqra, Sultan Husein; Mardani, Ali
ABSTRACT: In this study the effect of fiber type and utilization ratio on the dimensional stability and durability properties of pavement mortar mixtures was investigated. Three different fibers that are 12 mm long polypropylene, polyamide, and basalt fiber were used at a ratio of 0.25%, 0.50%, 0.75%, and 1% of their total volume. Drying-shrinkage, alkali-silica reaction (ASR), sulfate, freeze-thaw, and abrasion resistance of the mixtures were investigated. The findings to emerge from this study are as in the following: first, fiber addition prevented crack growth due to drying shrinkage of cementitious systems. Second, mixtures containing fiber showed higher performance in ASR and freeze-thaw whereas they underperformed in terms of sulfate resistance. These results could be attributed to a dual mechanism; on the one hand, the use of fiber is considered to create an additional void for the products that have the potential to form expansion to escape. On the other hand, the permeability of the mixtures increases as the void volume does due to the use of fiber. The former mechanism is considered to be predominant in ASR and freeze-thaw states. Specifically, mixtures containing basalt fiber with the highest modulus of elasticity outperformed in all properties.